The content of the second-generation curriculum for mathematics in intermediate education in Algeria includes some international standards (2000 NCTM) - Mekhelfi, Malika; Cherifi, Ali (Journal of Human Sciences, 2023)
The current study aims to find out the availability of the American National Council (NCTM 2000) international standards in the content of the math curriculum for the first, second and third year mathematics, for two areas: engineering, and measurement. The researcher used the descriptive analytical method, and the study sample consisted of the content of the second generation curriculum for mathematics for the first, second and third year of the average. The researcher used the content analysis tool, developed according to the US National Mathematics Standards (2000 NCTM), for content standards. The results of the study showed that the content of the second generation curriculum for mathematics for the first second and third year is average, which includes most of the NCTM standards for the fields of engineering and measurement in different proportions.